Pengembangan Supervisi Berbasis STEM untuk Meningkatkan Mutu Pembelajaran - Sriyanto Sriyanto (Action Research Journal, 2021)
The concept of supervision is basically the provision of assistance, the problem that arises is how to provide assistance to make students more capable, skilled in collaborating in science and technology so as to increase the effectiveness of the learning process in schools. This is in accordance with the principle of supervision according to Law Number 14 of 2005. From the field analysis, it shows that the existing supervision of learning is not in accordance with 21st century learning so that it is necessary to develop a STEM-based supervision model with learning syntax with a STEM-based approach that is possible to improve learning in the classroom. SD in order to improve the quality of education. Development is carried out through the stages of defining, planning and developing. The test was carried out using the SPSS validation test and field validation to determine the effectiveness of the STEM-based learning supervision instrument. The field trial design was carried out at 10 elementary schools in Petungkriyono District, Pekalongan Regency with sampling techniques using documentation, observation and questionnaires. The results of expert validation state that the STEM-based learning supervision development instrument is well developed and can be used with slight revisions, the results of which can be used by the principal to carry out supervision in improving the quality of learning.